2011
DOI: 10.1007/s10765-011-1087-7
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Viscosities, Speeds of Sound, and Refractive Indices of Binary Mixtures of 2-Octanol with Chlorobenzenes

Abstract: Densities, ρ, viscosities, η, speeds of sound, u, and refractive indices, n D , of binary liquid mixtures of 2-octanol with 1,2-dichlorobenzene, 1,3-dichlorobenzene, and 1,2,4-trichlorobenzene have been measured over the entire range of composition at 298.15 K, 303.15 K, and 308.15 K and at atmospheric pressure. From the experimental data of the density, speed of sound, viscosity, and refractive index, the values of the excess molar volume, V E , deviations in isentropic compressibility, κ S , and deviations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…b. ±2-Octanol (racemic mixture): (●) Mahajan, , (○) Daoudi, (▼) Bhatia, (△) Oswal, , (■) Bernazzani, (□) Bernazzani, (◆) Iloukhani, (◇) Iloukhani, (▲) Iloukhani, (▽) Aminabhavi, (⬢) Aminabhavi, (⬡) Bartolome, (★) Meghelli, (☆) Traynham, (⊕) Dorough, (⊞) Goering, (◩)­Kornblum . c. 1-Heptanol: (●) Dávila, (○) Garg, (▼) Zuñiga-Moreno, (△) Süelzner, (■) Alaoui, (□) Shakhverdiev, (◆) Golubev, (◇) Dzida, (▲) Cano-Gómez, (▽) Cao, (⬢) Uosaki, (⬡) Domańska …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b. ±2-Octanol (racemic mixture): (●) Mahajan, , (○) Daoudi, (▼) Bhatia, (△) Oswal, , (■) Bernazzani, (□) Bernazzani, (◆) Iloukhani, (◇) Iloukhani, (▲) Iloukhani, (▽) Aminabhavi, (⬢) Aminabhavi, (⬡) Bartolome, (★) Meghelli, (☆) Traynham, (⊕) Dorough, (⊞) Goering, (◩)­Kornblum . c. 1-Heptanol: (●) Dávila, (○) Garg, (▼) Zuñiga-Moreno, (△) Süelzner, (■) Alaoui, (□) Shakhverdiev, (◆) Golubev, (◇) Dzida, (▲) Cano-Gómez, (▽) Cao, (⬢) Uosaki, (⬡) Domańska …”
Section: Resultsmentioning
confidence: 99%
“…The thermal expansion and isothermal compressibility coefficient of ±2-octanol are shown in Figure 7a,b, respectively. We have compared our atmospheric values with those of Bernazzani et al 67 We have an average absolute percentage deviation from their values of 1.2% for κ T and 2.5% for α P at 298.15 K. Bhatia et al 64 report the thermal expansion coefficient at temperatures from 298.15 to 308.15 K. We have used their values to calculate the isothermal compressibility using…”
Section: Rt M T P Tmentioning
confidence: 99%
“…1.5 times larger Φ FL values in solution than C 6 Ph-HBT (Table 1). The obtained Φ FL values depend on viscosity 61−63 in nonpolar solvents such as toluene (η = 0.57 mPa s), 64 CH 2 Cl 2 (η = 0.41 mPa s), 65 1,2-C 6 H 4 Cl 2 (η = 1.31 mPa s), 66 and 1,2,4-C 6 H 3 Cl 3 (η = 1.93 mPa s). 66 EtOH/glycerol solutions with different mixing ratios also indicated a positive correlation between viscosity and Φ FL (Figure S4).…”
Section: ■ Experimental Sectionmentioning
confidence: 95%
“…The obtained Φ FL values depend on viscosity 61−63 in nonpolar solvents such as toluene (η = 0.57 mPa s), 64 CH 2 Cl 2 (η = 0.41 mPa s), 65 1,2-C 6 H 4 Cl 2 (η = 1.31 mPa s), 66 and 1,2,4-C 6 H 3 Cl 3 (η = 1.93 mPa s). 66 EtOH/glycerol solutions with different mixing ratios also indicated a positive correlation between viscosity and Φ FL (Figure S4). The dependence can be interpreted by the impact of an alkyne group on hampering the twisting of the central C−C bond.…”
Section: ■ Experimental Sectionmentioning
confidence: 95%
“…N,N-dimethylformamide has been widely used as a selective extractant solvent for xylene separation from naphtha feed. 1 Measurements of densities, viscosities, speeds of sound and other thermodynamic properties of binary mixtures of o-, m-, p-xylene and isopropyl benzene and 2-butanone, 9 pyridine, 10 1-decanol, 11 N,Ndiethylformamide, 8 1,7 We have studied o-, m-, p-xylene with pyridine at 293.15, 303.15, 313.15 and 323.15 K to determine inter-and intra-molecular interactions that exits in their binary mixtures 10 In this study, Experimental viscosities and densities are reported at four temperatures 293. 15 …”
Section: Introductionmentioning
confidence: 99%